2020
DOI: 10.1136/jitc-2019-000233
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of antitumor immunity through anti-MICA antibodies elicited with a chimeric protein

Abstract: BackgroundNatural killer and cytotoxic CD8+T cells are major players during antitumor immunity. They express NKG2D, an activating receptor that promotes tumor elimination through recognition of the MHC class I chain-related proteins A and B (MICA and MICB). Both molecules are overexpressed on a great variety of tumors from different tissues, making them attractive targets for immunotherapy. However, tumors shed MICA and MICB, and the soluble forms of both (sMICA and sMICB) mediate tumor-immune escape. Some rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…In addition to the effects on T lymphocytes, hypoxia also affects the function of natural killer (NK) cells. There is substantial evidence that hypoxia suppresses the cytotoxic effect of NK cells in tumors [101]. Upregulation of HIF-1α within the tumor can lead to decreased expression of the natural killer group 2 member D (NKG2D) receptor on NK and T cells, leading to immune evasion and impaired tumor cell killing [101,102].…”
Section: Hypoxia and The Immune Environmentmentioning
confidence: 99%
“…In addition to the effects on T lymphocytes, hypoxia also affects the function of natural killer (NK) cells. There is substantial evidence that hypoxia suppresses the cytotoxic effect of NK cells in tumors [101]. Upregulation of HIF-1α within the tumor can lead to decreased expression of the natural killer group 2 member D (NKG2D) receptor on NK and T cells, leading to immune evasion and impaired tumor cell killing [101,102].…”
Section: Hypoxia and The Immune Environmentmentioning
confidence: 99%
“…The direct impact of hypoxia on NK cells may involve HIF-1α upregulation via the activation of the phosphatidylinositol 3 kinase (PI3K)/mTOR signaling pathway [27]. Furthermore, hypoxic tumor cells, via HIF-1α, can upregulate the expression of the metalloproteinase ADAM10, which is responsible for the shedding of the natural killer group 2, member D (NKG2D) ligand major histocompatibility complex (MHC) class I chain-related molecule A (MICA) from the tumor cell surface [28]. Soluble MICA can downregulate the expression of the NKG2D activating receptor on NK and T cells, resulting in tumor evasion from the immune system [28].…”
Section: Hypoxia Reduces Functions Of Natural Killer and Natural Killmentioning
confidence: 99%
“…Furthermore, hypoxic tumor cells, via HIF-1α, can upregulate the expression of the metalloproteinase ADAM10, which is responsible for the shedding of the natural killer group 2, member D (NKG2D) ligand major histocompatibility complex (MHC) class I chain-related molecule A (MICA) from the tumor cell surface [28]. Soluble MICA can downregulate the expression of the NKG2D activating receptor on NK and T cells, resulting in tumor evasion from the immune system [28]. Moreover, hypoxia can downregulate the expression and function of the major activating NK-cell receptors (NK p30, NK p44, NK p46, and NKG2D).…”
Section: Hypoxia Reduces Functions Of Natural Killer and Natural Killmentioning
confidence: 99%
“…MICA is expressed in a wide variety of tumors ( 91 , 101 110 ). RNA sequencing (seq) data indicate that MICA is the NKG2DL that exhibits the highest expression in, from example, lung, colorectal, stomach, liver and breast cancers ( 111 ). Also, MICA exhibits a very low tumor mutational burden, suggesting that its expression is not subject to DNA editing to confer some kind of adaptive advantage to tumors.…”
Section: The Nkg2d Receptor and Its Ligandsmentioning
confidence: 99%
“…Prophylactic active immunization with BLS-MICA significantly delayed the growth of MICA-expressing tumors in part due to the ability to promote scavenging of sMICA from mouse sera. Passive immunization experiments demonstrated that such effect was mediated by anti-MICA Ab that mediated in vitro and in vivo ADCC, and that tilted the balance of tumor-infiltrating cells towards an anti-tumoral/pro-inflammatory phenotype characterized by an increased presence of TAM with an M1-skewed phenotype and antigen-experienced CTL ( 111 ). Therefore, immunization with BLS-MICA induced therapeutic anti-MICA Ab that constitute a “two-in-one” strategy as they promote tumor elimination by ADCC and interfere with a tumor immune escape through scavenging of sMICA.…”
Section: The Opportunity For the Nkg2d-nkg2dl Axis In Immuno-oncologymentioning
confidence: 99%